Bureaucratic Foreign Policy Model in Handling Humanitarian Conflict in Myanmar: Comparison between Sosilo Bambang Yudhoyono and Joko Widodo - Vivi Alayda Anwar; M. Syaprin Zahidi (Jurnal Studi Sosial dan Politik, 2023)
The humanitarian conflict in Myanmar, which has garnered worldwide attention due to its human rights violations and the resulting displacement of Rohingya people to neighbouring countries, including Indonesia. The conflict spanned two leadership periods: Susilo Bambang Yudhoyono (SBY) and Joko Widodo (Jokowi). However, there were notable differences in the foreign policies pursued by both leaders. The research aims to find out the differences in bureaucratic models between SBY and Jokowi that influenced their respective foreign policy approaches. The theoretical frameworks employed in this research include Graham T. Allison's theory of foreign policy formulation, the concept of bureaucracy put forth by Parkinson, and the notion of patrimonial bureaucracy. A descriptive qualitative approach was adopted for this research, utilizing a literature study method that drew from journals, articles, and other relevant sources. Data analysis was conducted in a descriptive and correlational manner to elucidate and explain the relationship between bureaucratic models and foreign policy decisions. The findings revealed disparities in the foreign policies pursued by Indonesia during the SBY and Jokowi administrations regarding the Rohingya conflict in Myanmar. These differences can be attributed, in part, to the variances in bureaucratic models adopted by the two leaders. SBY's leadership was characterized by a Parkinsonian bureaucracy, resulting in an outward-focused foreign policy approach. Conversely, Jokowi's leadership reflected a patrimonial bureaucracy, which tended to prioritize domestic concerns. However, it is important to note that bureaucratic models alone cannot serve as the sole basis for formulating foreign policy, as numerous other factors also exert influence.